Sleep and nutritional profile of endurance and ultra-endurance running athletes - Nadia Esteves dos Santos; Natalia Vilela Silva Daniel; Beatriz Franco; Andre Marana Bastos; Taisa Belli; Andrea Maculano Esteves (Sleep Science, 2022)
Sleeping and eating before and during an ultramarathon can directly affect an athlete’s performance, who may also have their physiological adaptations and recovery process hindered by sleeping problems. Endurance and ultra-endurance athletes may have different sleep and nutrition profiles. Thus, this study aimed to describe the sleep profile (during preparation) and nutritional profile (during competition) of endurance (10-20km) and ultra-endurance (50-100km) running athletes. For this, 16 healthy volunteers answered questionnaires related to sleep quality (Pittsburgh sleep quality index), chronotype (morningness-eveningness questionnaire), and sleepiness (excessive daytime sleepiness questionnaire). Immediately after a competition, a form prepared by the research team about nutritional variables and volunteers’ food records during the competition was applied. According to test scoring criteria (Pittsburgh sleep quality index >5; sleepiness >10), endurance running athletes showed low sleep quality. In addition, all athletes showed consumption of carbohydrates and lipids below the recommended, but excessive consumption of proteins. A positive association between sleepiness and sodium intake in endurance runners was observed (r=0.862; p=0.027). Sleep efficiency and race time showed a negative correlation only for ultra-endurance athletes (r=-0.834; p=0.039). The data obtained show that endurance athletes presented more sleep pattern alterations, however, endurance and ultra-endurance athletes showed inadequate nutritional consumption during the competition.